Local inhabitants' opinion about quality of life inside and outside the Triglav National Park - Jana ZURC; Andrej UDOVČ (Acta Agriculturae Slovenica)
Article presents results of a research made among local inhabitants inside and outside the Triglav National Park in Slovenia. Including the local inhabitants in the decision making process should have positive influence on further progress of the area. A poll was made among 200 residents for this purpose, in which we wanted to get inhabitants' opinion of quality of life in the area where they live. Results indicate that 36% of interviewees agree that their quality of life is good and 12% claim that it is very good. 68% of inhabitants strongly agree and 25% agree that their area of living needs better employment chances.